Simple Experiments for Introducing Science to Elementary School Students - Ali Rahmat (ASEAN Journal of Science and Engineering Education, 2021)
The purpose of this paper is to introduce some simple experiments that can be used to explain science to elementary school students. This study explained about seven experiments that can be done easily and used simple materials (found in daily life). This paper also explains the scientific reasons for the phenomena happening during the teaching and learning process.